HUBUNGAN PENGGUNAAN SMARTPHONE DENGAN KUALITAS TIDUR REMAJA DI SMA NEGERI 2 TUALANG KABUPATEN SIAK TAHUN 2023 - Yuyun Priwahyuni; Rara Rahmadani; Herlina Susmaneli; Christine Vita Gloria Purba; Emy Leonita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Sleep quality is the condition in which a person sleeps and then feels fresh and fit when waking up. Poor sleep quality can cause a person to be unhealthy and easily get sick. The prevalence of sleep disorders among adolescents in Indonesia is 37.7% in suburban areas and around 38% in urban areas. One of the factors that affect sleep quality is the use of smartphones. The purpose of this study was to determine the relationship between smartphone use and adolescent sleep quality at SMA Negeri 2 Tualang, Siak Regency in 2023. This study uses quantitative research methods with a cross sectional design. The sampling technique used was stratified random sampling. The population in this study were 768 students with a sample of 209 students. The analysis used in this study was univariate and bivariate analysis using the chi square test. The results showed that there was a relationship between the duration of smartphone use (p=0.0001), smartphone addiction (p=0.010), social media use (p=0.0001), online game addiction (p = 0.0001) with adolescent sleep quality. From these results it can be concluded that the use of smartphones is associated with adolescent sleep quality. It is expected that adolescents can maximize sleep hours at night. Keywords: Smartphone Usage, Sleep Quality, Social Media, Online Games, Teenagers